Arboreal structure in hydrological regimes present in a gallery forest of northeast Mexico - Amaran-Ruiz, María de Fátima; Alanís-Rodríguez, Eduardo; García-Espinoza, Guadalupe Geraldine; Graciano-Ávila, Gabriel; Mata-Balderas, José Manuel; Luna-Robles, Armando Alberto (Ecosistemas y Recursos Agropecuarios, 2024)
The structure and diversity of woody species in different types of watercourses along the Santa Catarina river in Nuevo Leon, Mexico were described. Three conditions were identified: permanent (I), semi-permanent (II) and temporary (III). In each condition, 14 rectangular sites of 1000 m2 were established. All woody species (d0.10 m > 5 cm) were identified. The crown diameter of each individual was measured. The Importance Value Index (IVI) was determined for each condition; considering the abundance, crown dominance and frequency of the species. Species richness and diversity was calculated with the Margalef (DMg) and Shannon-Weiner (H´) indices. In addition, the similarity between conditions was determined using the Sorensen index (Is). 32 species, 29 genera and 16 families were identified. Salix nigra Marshall presented the highest IVI in condition I and II, while Leucaena leucocephala Lam. in condition III. Condition I registered greater specific richness and greater diversity with 28 species and an H´ value = 2.41 ± 0.710. Condition II presented the highest Margalef richness with a DMg value = 1.77 ± 0.22. The similarity between conditions was greater than 50 %. The results demonstrate the structural variation of the vegetation in different hydrological regimes, which constitutes a solid base for future investigations on the development of the vegetation associated with the Santa Catarina river, and other riparian areas of northern Mexico.